News-Driven Inflation Expectations and Information Rigidities - Vegard Høghaug Larsen; Leif Anders Thorsrud; Julia Zhulanova (Norges Bank, 2019)
We investigate the role played by the media in the expectations formation process of households. Using a novel news-topic-based approach we show that news types the media choose to report on, e.g., fiscal policy, health, and politics, are good predictors of households' stated inflation expectations. In turn, in a noisy information model setting, augmented with a simple media channel, we document that the underlying time series properties of relevant news topics explain the time-varying information rigidity among households. As such, we not only provide a novel estimate showing the degree to which information rigidities among households varies across time, but also provide, using a large news corpus and machine learning algorithms, robust and new evidence highlighting the role of the media for understanding inflation expectations and information rigidities.
hdl:11250/2591007
Keywords: C11; C53; D83; D84; E13; E31; E37; 330